Facilitating Reparative Dentin Formation Using Apigenin Local Delivery in the Exposed Pulp Cavity - Aryal, Yam Prasad; Yeon, Chang-Yeol; Kim, Tae-Young; Lee, Eui-Seon; Sung, Shijin; Pokharel, Elina; Kim, Ji-Youn; Choi, So-Young; Yamamoto, Hitoshi; Sohn, Wern-Joo; Lee, Youngkyun; An, Seo-Young; et al. (Frontiers in Physiology, 2021)
Apigenin, a natural product belonging to the flavone class, affects various cell physiology, including cell signaling, inflammation, proliferation, migration, and protease production. In this study, apigenin was applied to mouse molar pulp after mechanically pulpal exposure to examine the apigenin’s detailed function in regulating pulpal inflammation and tertiary dentin formation. In-vitro cell cultivation using human dental pulp stem cells (hDPSCs) and in-vivo mice model experiments were employed to examine the effect of apigenin in the pulp and dentin regeneration. In-vitro cultivation of hDPSCs with apigenin treatment upregulated BMP-and osteogenesis-related signaling molecules including BMP2, BMP4, BMP7, RUNX2 and OCN after 14 days. After apigenin local delivery in the mice pulpal cavity, histology and cellular physiology, including modulation of inflammation and differentiation, were examined using histology and immunostainings. Apigenin-treated specimens showed period-altered immunolocalization patterns of TNF-α, MPO, NESTIN, and TGF-β1 at three and five days. Moreover, apigenin-treated group showed a facilitated dentin-bridge formation with few irregular tubules after 42 day from pulpal cavity preparation. Micro-CT images confirmed obvious dentin-bridge structures in the apigenin-treated specimens compared with the control. Apigenin facilitated reparative dentin formation through modulation of inflammation and activation of signaling regulations. Therefore, apigenin would be a potential therapeutic agent for regenerating dentin in exposed pulp caused by dental caries and traumatic injury.